Marco conceptual de la renovación urbana (2014)
This paper presents a first approach to the concepts, processes and criteria that have developed some plans for Urban Renewal in Europe, reaching proposals led by the District of Bogota in the area known as Triangle Phoenicia. It is part of knowing the conditions which determine these urban renewal plans that promote “habitat enhancement site” and yet rarely point to end processes, letting it be especially led by the economic variable.